HIV-1 Drug Resistance by Ultra-Deep Sequencing Following Short Course Zidovudine, Single-Dose Nevirapine, and Single-Dose Tenofovir with Emtricitabine for Prevention of Mother-to-Child Transmission. (1st December 2016) - Samuel, Reshmi; Julian, Marc Noguera; Paredes, Roger; Parboosing, Raveen; Moodley, Pravi; Singh, Lavanya; Naidoo, Anneta; Gordon, Michelle
Abstract : Abstract: Antiretroviral drug resistance following pMTCT strategies remains a significant problem. With rapid advancements in next generation sequencing technologies, there is more focus on HIV drug-resistant variants of low frequency, or the so-called minority variants. In South Africa, AZT monotherapy for pMTCT, similar to World Health Organization option A, has been used since 2008. In 2010, a single dose of co-formulated TDF/FTC was included in the strategy for prevention of resistance conferred by single-dose nevirapine (sd NVP). The study was conducted in KwaZulu-Natal, South Africa, among pMTCT participants who received AZT monotherapy from 14 weeks of gestation, intrapartum AZT and sd NVP, and postpartum sd TDF/FTC. Twenty-six specimens collected at 6 weeks post-delivery were successfully sequenced using 454 ultra-deep sequencing. Non-nucleoside reverse transcriptase inhibitor (NNRTI) resistance was detected in 17 of 26 (65%) patients, 2 (7%) had Thymidine analogue mutations, and 3 (11%) had K65R. Of the 17 patients with NNRTI resistance, 11 (65%) had high-level NNRTI resistance, whereas 6 (35%) had intermediate NNRTI resistance. The levels of NNRTI resistance are much higher than would be expected, given the inclusion of antepartum AZT and postpartum TDF/FTC. This high level of NNRTI resistance could impact future NNRTI-containing treatment for a large proportion of pMTCT-exposed women. The detection of Thymidine analogue mutations highlights the need to understand the clinical impact of these on AZT-containing antiretroviral treatment in women exposed to AZT monotherapy. Abstract : Supplemental Digital Content is Available in the Text.